Crucial role of neutrophils in the development of mechanical inflammatory hypernociception - Cunha, Thiago M.; Verri, Waldiceu A.; Schivo, Ieda R.; Napimoga, Marcelo H.; Parada, Carlos A.; Poole, Stephen; Teixeira, Mauro M.; Ferreira, Sergio H.; Cunha, Fernando Q. (Journal of leukocyte biology, 2008)
Neutrophil migration is responsible for tissue damage observed in inflammatory diseases. Neutrophils are also implicated in inflammatory nociception, but mechanisms of their participation have not been elucidated. In the present study, we addressed these mechanisms in the carrageenan‐induced mechanical hypernociception, which was determined using a modification of the Randall‐Sellito test in rats. Neutrophil accumulation into the plantar tissue was determined by the contents of myeloperoxidase activity, whereas cytokines and PGE2 levels were measured by ELISA and radioimmunoassay, respectively. The pretreatment of rats with fucoidin (a leukocyte adhesion inhibitor) inhibited carrageenan‐induced hypernociception in a dose‐ and time‐dependent manner. Inhibition of hypernociception by fucoidin was associated with prevention of neutrophil recruitment, as it did not inhibit the hypernociception induced by the direct‐acting hypernociceptive mediators, PGE2 and dopamine, which cause hypernociception, independent of neutrophils. Fucoidin had no effect on carrageenan‐induced TNF‐α, IL‐1β, and cytokine‐induced neutrophil chemoattractant 1 (CINC‐1)/CXCL1 production, suggesting that neutrophils were not the source of hypernociceptive cytokines. Conversely, hypernociception and neutrophil migration induced by TNF‐α, IL‐1β, and CINC‐1/CXCL1 was inhibited by fucoidin, suggesting that neutrophils are involved in the production of direct‐acting hypernociceptive mediators. Indeed, neutrophils stimulated in vitro with IL‐1β produced PGE2, and IL‐1β‐induced PGE2 production in the rat paw was inhibited by the pretreatment with fucoidin. In conclusion, during the inflammatory process, the migrating neutrophils participate in the cascade of events leading to mechanical hypernociception, at least by mediating the release of direct‐acting hypernociceptive mediators, such as PGE2. Therefore, the blockade of neutrophil migration could be a target to development of new analgesic drugs.